Kewenangan Pemerintah Daerah dalam Penegakan Pengawasan Lingkungan Limbah Bahan Berbahaya dan Beracun - Muhamad Rafa Afiandra; Efik Yudiansyah; Fabian Fadhly Jambak (Bandung Conference Series: Law Studies, 2024)
Abstract. Waste is a hazardous liquid that is disposed of in a certain place that can damage the environment around waste, contains pollutants that are toxic and dangerous. This waste is known as B3 (Hazardous and Toxic Materials) waste. This material is formulated as a relatively small amount of material but has the potential to pollute / damage the living environment and resources. As waste, its presence is quite worrying, especially those sourced from industry. For this reason, a correct process is needed to process waste so that it is not harmful to the environment. Industrial factories should also have permits that have been set by the government so that they always obey and comply with existing regulations. To facilitate processing and monitoring, waste treatment requires sophisticated control equipment in the form of a programmable logic controller (PLC). The method of approach to this research uses normative juridical, namely by researching secondary literature materials/data. The specification of this study uses a descriptive analysis method, namely describing legislation with legal theories. The data collection technique uses document studies and field research. Research Data Collection is carried out by searching and collecting data both from legislation, literature, interviews, and related to the problem being researched. Data Processing Through data that has been obtained and collected from literature or books, interview results and information related to the right to a healthy environment for the community Abstrak. Limbah adalah cairan berbahaya yang di buang pada suatu tempat tertentu yang dapat merusak lingkungan sekitar limbah mengandung bahan pencemar yang bersifat racun dan bahaya. Limbah ini dikenal dengan limbah B3 (Bahan Berbahaya dan Beracun). Bahan ini dirumuskan sebagai bahan dalam jumlah relatif sedikit tapi mempunyai potensi mecemari /merusak lingkungan kehidupan dan sumber daya. Sebagai limbah kehadirannya cukup mengkhawatirkan terutama yang bersumber dari industri. Untuk itu diperlukan suatu proses yang benar untuk mengolah limbah agar tidak berbahaya bagi lingkungan. Pabrik industri pun seharusnya memiliki perizinan yang telah ditetapkan oleh pemerintahan agar selalu menaati dan mematuhi peratiran yang ada. Untuk mempermudah pengolahan dan monitoring, pengolahan limbah diperlukan alat pengontrol yang canggih berupa programmable logic controller (PLC). Metode pendekatan penelitian ini menggunakan yuridis normatif yaitu dengan meneliti bahan pustaka/data sekunder. Spesifikasi penelitian ini menggunakan metode deskritif analisis yaitu menggambarkan perundang-undangan dengan teori-teori hukum. Teknik pengumpulan data menggunakan studi dokumen dan penelitian lapangan. Pengumpulan Data Penelitian dilakukan dengan cara mencari dan mengumpulkan data baik dari perundang-undangan, literatur, wawancara, maupun yang berkaitan dengan masalah yang diteliti. Pengolahan Data Melalui data yang telah diperoleh dan dikumpulkan dari literatur atau buku-buku, hasil wawancara dan keterangan-keterangan yang berkaitan dengan hak atas lingkungan hidup yang sehat bagi masyarakat.